Enchancing SMEs Competitiveness Through Business Legality (NIB) And Digital Marketing In Tembelang Village - Ninis Umnastuti; Dewi Puspitaningsih; Muhammad Arif Zikir Risky; Nurianah; Beni Sucipto; Lala Hucadinota Ainul Amri (Universitas AMIKOM Yogyakarta, 2025)
Microenterprises owned by housewives in Tembelang Village, Jombang Regency, considerable growth potential, however they remain constrained by limited business legality and optimalization of digital technologies, which in turn restrict access to financial institutions and government support programs. This Community Service initiative aims to enhance to competitiveness of SMEs through the facilitation of Business Indentification Number (NIB) registration and the provision of digital marketing training, involving housewives engaged in microenterprises as primary participants. The implementation a structured approach comprising needs assessment, training on NIB registration and digital marketing, hand on assistance until NIB issuance, and program evaluation. The findings indicate that prior to the intervention, around 80% of participants did not possess an NIB and 70% had not utilized digital platforms for marketing purposes. Following the intervention, around 70% of participants successfully abtained an NIB, while more than 60% initiated the use of social media as a marketing channel. The program contributed to improved access to funding opportunities and broader market reach. Nevertheless, several limitations were indentified, including the relatively limited duration of the training and disparities in participants technological adaptability. Overall, this initiative a positive contribution to strengthening business legality and the digital marketing capabilities of SMEs in a sustainable.